Cadherin-11 Regulates Macrophage Development and Function - To, Sarah; Chavula, Thandiwe; Pedroza, Mesias; Smith, Jennifer; Agarwal, Sandeep K. (Frontiers in Immunology, 2022)
Cadherin-11 (CDH11) is a cell-cell adhesion protein that has previously been reported to play an important role in the pathogenesis of pulmonary fibrosis. It is expressed on macrophages in the fibrotic lung. However, the role of CDH11 on macrophage biology has not yet been studied. We show using immunophenotypic analyses that Cdh11-/- mice have fewer recruited monocyte-derived macrophages and Ly6Chi monocytes in the lungs compared to wild-type mice in the intraperitoneal bleomycin-induced fibrosis model. Additionally, fewer Ly6Chi monocytes were detected in the bone marrow and peripheral blood of naive Cdh11-/- mice. Given that macrophages are derived from monocytes, we investigated the precursors of the monocyte/macrophage lineage in the bone marrow. We found increased numbers of CMPs and reduced numbers of GMPs and MPs/cMoPs in Cdh11-/- mice compared to wild-type mice, suggesting decreased differentiation towards the myeloid lineage in the Cdh11-/- mice. Accordingly, we show using bone marrow cells that loss of CDH11 impaired monocyte to macrophage differentiation. We also show CDH11 deficiency repressed the M2 program and impaired the phagocytic function of bone marrow-derived macrophages. Thus, our findings demonstrate a role for CDH11 in macrophage development, M2 polarization, and phagocytic function.